MENGKAJI KEPUASAN DAN LOYALITAS KONSUMEN SUSU BUBUK TINGGI KALSIUM DENGAN PENDEKATAN MULTI-ATRIBUT - Amam Rafael; Pradiptya Ayu Harsita (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Constumer satisfaction and loyalty is one indicator of marketing success. This study aimed to analyze the level of customer satisfaction and loyalty milk powder with high calcium by attributes attached to high calcium milk powder products. Milk powder used as the object of the research was Anlene milk powder and Hilo milk powder. Attributes used in the study are: brand, flavour, label, price, and promotion. Determination of the sample using multistage sampling technique. The data analysis used is multiple linear regression. The results showed that milk powder Anlene attributes that affect customer satisfaction is a flavor of (0,001), price (0,018), and promotion (0,023), while milk powder Hilo attributes that affect customer satisfaction is the brand (0,024) and the label (0,015). Anlene milk powder attributes that influence consumer loyalty is priced at 0,017, while the milk powder Hilo attributes that influence consumer loyalty is the brand of 0,021.